Perception of the operating agents about the Brazilian National School Feeding Program - Daniele Mendonça Ferreira; Roseane Moreira Sampaio Barbosa; Nathália Corrêa Finizola; Daniele da Silva Bastos Soares; Patrícia Henriques; Silvia Pereira; Clarice Soares Carvalhosa; Ana Beatriz Franco Sena Siqueira; Patricia Camacho Dias (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE Identify the perception operating agents have on the Brazilian National School Feeding Program. METHODS This is an observational, cross-sectional and quali-quantitative study developed in non-probability and convenience sampling selected in an event promoted by the National Fund for Educational Development in 2015 in Rio de Janeiro. Data were collected through questions related to pre-defined categories concerning the National School Feeding Program. The questionnaire was answered by 43 nutritionists, 41 members of the School Feeding Board, and 16 school feeding administrators from 38 cities of Rio de Janeiro. The narrative analysis was based on benchmarks of cognitive analysis of public policies. The association among variables was investigated with chi-square test, being calculated the power for association testing. RESULTS The perception of the implementation of the National School Feeding Program has been characterized by some challenges: 1) low number of nutritionists to meet the demand from schools; 2) low adhesion to the public call for the purchase of family farming products due to bureaucratic difficulties and insufficient local food production; 3) reduced coverage of food and nutritional measures due to the restriction of human, material and financial resources; and 4) limitation of the participation of the School Feeding Board due to insufficient training and transport for regular visits. The adequacy of the number of nutritionists showed statistically significant association with the purchase of family farming products (p = 0.002; power = 99%) and with the food and nutritional education activities (p = 0.021; power = 79%). CONCLUSIONS The results indicate the need for employment of nutritionist in sufficient numbers to meet the demands of the National School Feeding Program, investment in educational activities of healthy eating in schools, training of the School Feeding Board, greater availability of vehicles for school visits and assistance to family farmers in order to facilitate their participation in programs of institutional purchases and encourage the diversification of production.